“Conocimiento y actitud sobre cloruro de cetilpiridinio para control del COVID-19 en alumnos de Estomatología – UNT, 2021” - Barrantes Rafael, Jhonell Yampier (2022)
The purpose of this basic, observational, descriptive and cross-sectional research is to find the knowledge and attitude about Cetylpyridinium Chloride (CPC) for the control of the viral load of COVID-19 in Stomatology students - UNT, 2021. The sample consisted of 130 students from the Stomatology Faculty of the National University of Trujillo who participated voluntarily, of the total 88 were female (67.7%) and 4 male (32.30%); In addition, 17 students correspond to the first year (13.07%), 20 to the second year (15.4%), 25 to the third year (19.23%), 12 to the fourth year (9.23%), 23 to the fifth year (17.69%) and 33 of sixth year (25.38%). The results were that the level of knowledge about CPC for the control of COVID-19 in Stomatology students - UNT, 2021 was 4.6% with the "Very low" level, 30.8% with the "Low" level, 21.5% with the “Fair”, 30.8% with the “High” level and finally 12.3% with the “Very high” level. While the attitude was 2.3% with the "Negative" level, followed by 40% with the "Indifferent" level and finally 57.7% with the "Positive" level. From this research work, it is concluded that the level of knowledge about CPC for the control of COVID-19 in Stomatology students - UNT, 2021 was "Low" for a group of respondents who represented 30.8% and in the same way it was found that was “High” for a similar group of respondents who represented 30.8% of the sample, while attitude was “positive” (57.7%).